White matter microstructure, cognition, and molecular markers in fragile X premutation females. (30th May 2017) - Shelton, Annie L.; Cornish, Kim M.; Godler, David; Bui, Quang Minh; Kolbe, Scott; Fielding, Joanne
Abstract : Objective: To examine the interrelationships between fragile X mental retardation 1 ( FMR1 ) mRNA and the FMR1 exon 1/intron 1 boundary methylation, white matter microstructure, and executive function, in women with a FMR1 premutation expansion (PM; 55–199 CGG repeats) and controls (CGG < 44). Methods: Twenty women with PM without fragile X-associated tremor/ataxia syndrome (FXTAS) and 20 control women between 22 and 54 years of age completed this study. FMR1 mRNA and methylation levels for 9 CpG sites within the FMR1 exon 1/intron 1 boundary from peripheral blood samples were analyzed. To measure white matter microstructure, diffusion-weighted imaging was used, from which fractional anisotropy (FA) and mean diffusivity (MD) values from anatomic regions within the corpus callosum and cerebellar peduncles were extracted. Executive function was assessed across a range of tasks. Results: No differences were revealed in white matter microstructure between women with PM and controls. However, we reveal that for women with PM (but not controls), higher FMR1 mRNA correlated with lower MD values within the middle cerebellar peduncle and Paced Auditory Serial Addition Test scores, higher methylation of the FMR1 exon 1/intron 1 boundary correlated with lower MD within the inferior and middle cerebellar peduncles and longer prosaccade latencies, and higher FA values within the corpus callosum and cerebellar peduncle regions corresponded to superior executive function. Conclusions: We provide evidence linking white matter microstructure to executive dysfunction and elevated FMR1 mRNA and FMR1 exon 1/intron 1 boundary methylation in women with PM without FXTAS. This suggests that the FXTAS phenotype may not be distinct but may form part of a spectrum of PM involvement.